2018
DOI: 10.1017/s1049023x18000304
|View full text |Cite
|
Sign up to set email alerts
|

Skills and Core Competencies of Pharmacists in Humanitarian Assistance

Abstract: Self-management in a pressured and changing environment, the ability to adapt to changing situations, and planning, prioritizing, and performing tasks well under pressure are the skills required for pharmacists and for any other humanitarian health worker. The results highlight great efforts being dedicated to pharmaceutical product supply and management by pharmacists working in HA. VardanyanH, MoseguiGBG, MirandaES. Skills and core competencies of pharmacists in humanitarian assistance. Prehosp Disaster Med.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The views of employers in the focus group methodology used by Palermo et al were included to ensure that the competency framework conveyed the professionalism required of the future dietetic workforce ( 21 ). Vardanyan et al reported using interview methodology to explore the perspective of medical co-ordinators on the personal and managerial skills required of pharmacists ( 74 ).…”
Section: Resultsmentioning
confidence: 99%
“…The views of employers in the focus group methodology used by Palermo et al were included to ensure that the competency framework conveyed the professionalism required of the future dietetic workforce ( 21 ). Vardanyan et al reported using interview methodology to explore the perspective of medical co-ordinators on the personal and managerial skills required of pharmacists ( 74 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other areas like pharmaceutical care, health education, and health promotion can also be included in the training of these professionals, with the intent to qualify them to respond in the most efficient way in a future event. 34,35 It is important to keep records of the trainings. From these data, it is possible to follow the quantity of qualified personnel, and to plan training activities.…”
Section: Discussionmentioning
confidence: 99%
“…Use of team approaches Bryson et al,(2014), Pfleger et al,(2008), Diaz-Cruz,(2019), Johnson & Traynor,(2018), Fritsch et al,(2016, , NHS,(2014), Devraj et al,(2010), Saini et al,(2011), Woodard et al,(2016), Um et al,(2013), Dean et al,(2014), Jarvis et al,(2004), Walsh et al,(2012), Crane et al,(2010), Abraham et al,(2012), Martin et al,(2019), , Bradley et al,(2015, Pfleger et al,(2008), Diaz-Cruz,(2019), NHS,(2014), Healthy People Curriculum Task Force,(2020), Packard et al,(2010, , Holden & Evans,(2019), Lee,(2019), , Boyle et al,(2004), Teng et al,(2016) Healthy People Curriculum Task Force,(2020), Devraj et al,(2010), Earl et al,(2019), Lee,(2019) Bryson et al,(2014), Pfleger et al,(2008), Strand & Miller,(2014), , Johnson & Traynor,(2018), Vardanyan et al,(2018), NHS,(2014), Devraj et al,(2010), Packard et al,(2010), Chen et al,(2013), Kristina et al,(2018), Holden & Evans,(2019), Um et al,(2013), Markenson et al,(2005), Crane et al,(2010), Abraham et al,(2012), , Haddad et al,(2012), Pontefract & Wilson,(2019), Boyle et al,(2004),…”
Section: Use Of Communication Techniques Based On Theorymentioning
confidence: 99%
“…Public health skills of importance in this domain related to participation in health promotion and disease prevention activities. The consideration of health literacy in consumers was also highlighted as important for all pharmacy interactions (Poirier et al, 2009;Chen et al, 2013;Coleman et al, 2013;Bryson et al, 2014; J.R. Covvey & Ryan, 2018;Vardanyan et al, 2018;Earl et al, 2019).…”
Section: Medicines Management and Patient Carementioning
confidence: 99%
See 1 more Smart Citation